Could Elements of Hydraulics Cure the Ills of Contemporary Science? - Scalera, Giancarlo (European Journal of Applied Sciences, 2023)
The mechanical-engineering explanation for the gravitational field proposed by Johann Bernoulli (1667-1748) in the field of hydraulics is reconsidered. This is integrated with the resolution of a historic discomfort about sink and source singularities, achieved by applying the expanding Earth hypothesis and considering the recent Borexino and KamLAND experiments on the Earth's heat balance. This approach may resolve numerous issues in modern science, unifying multiple phenomena into a new non-Newtonian physics. In this new conception, gravitation, redshift, and expansion of celestial bodies are caused by Bernoulli's central torrent, while the principles of inertia, escape velocity, invariability of physical constants, etc. are relegated to good local approximations of a more complex physical reality.